Improving Mathematics Learning Outcomes Using the Make A Match Learning Model with Number Cards - Eko Pujianto; Stève Nimpagaritse (Yayasan Pendidikan Dan Pengembangan Harapan Ananda, 2026)
Mathematics remains one of the most challenging subjects for students, particularly in teacher education programs, where mastery is essential not only for academic success but also for future pedagogical practice. Conventional teacher-centered methods often fail to promote active engagement and deep conceptual understanding, underscoring the need for innovative approaches that combine interaction, collaboration, and enjoyable learning experiences. This study aimed to improve students’ mathematics learning outcomes through the implementation of the Make A Match learning model supported by number cards. The research employed a classroom action research design conducted in two cycles, each comprising the stages of planning, action, observation, and reflection. The participants were 28 undergraduate students enrolled in the Department of Primary School Teacher Education, Universitas Doktor Nugroho Magetan. Data were collected using formative tests, observation sheets, and field notes, and were analyzed through both quantitative and qualitative approaches. The findings demonstrated a consistent improvement in students’ learning outcomes. The mean score increased from 60.71 in the pre-cycle to 72.14 in Cycle I and 83.57 in Cycle II. Similarly, the percentage of students achieving mastery rose from 42.86% in the pre-cycle to 71.43% in Cycle I and 89.29% in Cycle II. Qualitative data supported these results, indicating enhanced engagement, collaboration, and active participation during learning activities. In conclusion, the Make A Match learning model with number cards effectively improved both the process and outcomes of mathematics learning. The study suggests that this strategy not only strengthens mathematical achievement but also fosters essential skills such as cooperation, communication, and problem-solving, making it a promising pedagogical approach for teacher education contexts.